Is Capping Executive Bonuses Useful? - Asai, Kentaro (IMF Working Papers; Working Paper ;, 2016)
This paper develops a theoretical framework to study the impact of bonus caps on banks' risk taking. In the model, labor market price adjustments can offset the direct effects of bonus caps. The calibrated model suggests that bonus caps are only effective when bank executives' mobility is restricted. It also suggests, irrespective of the degree of labor market mobility, bonus caps simultaneously reduce risk shifting by bank executives (too much risk taking because of limited liability), but aggravate underinvestment (bank executives foregoing risky but productive projects). Hence, the welfare effects of bonus caps critically depend on initial conditions, including the relative importance of risk shifting versus underinvestment.